2000
DOI: 10.2105/ajph.90.12.1933
|View full text |Cite
|
Sign up to set email alerts
|

Trends in crime and the introduction of a needle exchange program

Abstract: OBJECTIVES: This study sought to determine whether introduction of a needle exchange program would be associated with increased crime rates. METHODS: Trends in arrests were compared in program and nonprogram areas before and after introduction of a needle exchange program in Baltimore. Trends were modeled and compared via Poisson regression. RESULTS: No significant differences in arrest trends emerged. Over the study period, increases in category-specific arrests in program and nonprogram areas, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…This result is in line with other studies that have documented that fears associated with expanded syringe access, such as increased crime, drug use, and even needle stick injuries are unwarranted (Des Jarlais et al, 1995; Guydish et al, 1993; Marx et al, 2000; Stopka et al, 2010). Life-saving interventions such as needle exchange programs, over-the-counter pharmacy sales of needles, and overdose prevention programs for people who inject drugs are often political controversial and unpopular, yet are desperately needed to prevent overdose deaths, HIV and HCV transmissions.…”
Section: Discussionsupporting
confidence: 89%
“…This result is in line with other studies that have documented that fears associated with expanded syringe access, such as increased crime, drug use, and even needle stick injuries are unwarranted (Des Jarlais et al, 1995; Guydish et al, 1993; Marx et al, 2000; Stopka et al, 2010). Life-saving interventions such as needle exchange programs, over-the-counter pharmacy sales of needles, and overdose prevention programs for people who inject drugs are often political controversial and unpopular, yet are desperately needed to prevent overdose deaths, HIV and HCV transmissions.…”
Section: Discussionsupporting
confidence: 89%
“…The Getis-Ord Gi* analysis was based on a fixed Euclidean distance band of 3000 m. This distance was derived from a previous analysis of this population indicating 3 km to be a natural break point in the data with respect to intra-urban mobility (Brouwer et al 2012). It is also the distance an average person walks in 30–40 minutes (Knoblauch, Pietrucha and Nitzburg 1996; Marx et al 2000), which is how most of our participants travel. Results were corrected for multiple testing using the False Discovery Rate statistic (Benjamini and Hochberg 1995; Castro and Singer 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found that NEPs do not increase drug use (Burring, 1991; Normand, Vlahov, & Moses, 1995; Vlahov et al 2001) or incite youth to start injecting drugs (Marx, Brahmbhatt, Beilenson, et al , 2001). Moreover, NEPs have not been shown to increase numbers of publicly discarded syringes (Doherty, Junge, Rathouz, et al , 2000), crime (Marx, Crape, Brookmeyer et al , 2000), or high risk social networks (Schechter, Strathdee, Cornelisse, et al 1999; Lamothe, Bruneau, Franco, et al , 1998). Yet despite the established effectiveness of NEPs, they must be implemented to scale to achieve population level reductions in HIV incidence.…”
Section: Introductionmentioning
confidence: 99%